Investigations on anti-inflammatory and analgesic activities of Alnus nitida Spach (Endl). stem bark in Sprague Dawley rats. (23rd February 2017) - Sajid, Moniba; Khan, Muhammad Rashid; Shah, Sayed Afzal; Majid, Muhammad; Ismail, Hammad; Maryam, Sonia; Batool, Riffat; Younis, Tahira
Abstract: Ethnopharmacological relevance: S tem bark of Alnus nitida (Spach) Endl. (family Betulaceae) is used by local communities in northern areas of Pakistan as a remedy for swelling, injuries and pain. However no pharmacological study of this plant has been reported to confirm these activities. In this study anti-inflammatory and analgesic effect of A. nitida stem bark have been evaluated. Methods: Powder of the stem bark of A. nitida was extracted with methanol (ANBM) and partitioned in escalating polarity to get the n-hexane (ANBH), chloroform (ANBC), ethyl acetate (ANBE) and the residual soluble aqueous (ANBA) fractions. The methanol extract and derived fractions were evaluated for anti-inflammatory activity by using in vitro heat induced albumin denaturation assay and various in vivo assays; carrageenan-induced hind paw edema method, Freunds' complete adjuvant induced arthritis, histamine induced paw edema and xylene induced ear edema in Sprague Dawley rat. The extracts/fractions were also evaluated for analgesic effects by using hot plate analgesic test and acetic acid induced writhing test in rat. The ANBM composition was analyzed by HPLC-DAD and GC-MS analysis. Results: Results of heat induced albumin denaturation activity indicated that among the extract/fractions ANBC at concentration range of 100−500 µg/ml remarkably protected the heat induced albumin denaturation. The pretreatment with ANBC significantly reduced the carrageenan induced edema with 90.81±1.6% after 4 h, comparing with 86.63±3.42% reduction produced by the reference drug diclofenac potassium. Histopathological alterations of the gastric and hind paw were decreased with the extract/fractions. Furthermore, anti-inflammatory effects of ANBC were evident in Freunds' complete adjuvant induced arthritis, histamine induced paw edema and xylene induced ear edema. The latency time in hot plate analgesic assay with ANBC (61.59±0.38%) after 90 min was comparable to standard drug morphine (69.31±2.67%) and aspirin (67.24±2.08%). Similarly ANBC significantly (p<0.01) inhibited the pain sensation in acetic acid induced writhing test in rat. HPLC-DAD analysis of ANBM indicated the presence of gallic acid, catechin and rutin while the GC-MS analysis of ANBM indicated the presence of 30 compounds predominantly of neophytadiene, 3, 7, 11, 15 tetramethyl-2-hexadecen-1-ol, phytol, vitamin E and linalool. Conclusion: The results of this study suggested that the presence of polyphenols, sterols, terpenoids and other constituents might contributed towards the anti-inflammatory and analgesic activities of the crude methanol extract of A. nitida bark and its derived fractions. This study endorsed the folklore use of A. nitida bark for inflammation related disorders. Graphical abstract: